THE FOLKLORE AND MYTHOLOGICAL WORLD OF MARK CHEREMSHYNY - Zalevska, Oksana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the peculiarities of the folklore and mythological thinking of Mark Cheremshina, the identity of his author’s ideological and aesthetic consciousness. The literary works of the writer are analyzed, in which attention is focused on the figurative and symbolic interpretation of the Hutsul world, his assimilation and masterful transformation of the folkloric, mythological and ethnographic realities of the Hutsul region into the artistic line of novels and short stories, folklore-mythological and etnographic realities of Hutsul region its customs, rites, beliefs, incantations and spells, carols, folk song creativity, the important features of the writer’s style are determined, the ideological orientation and problematic of the prose are outlined, the attention is focused on the artistic display of both the external life and the internal state of the heroes of Mark Cheremshina’s short prose. The mythological world of the writer is realized in the texts through binary oppositions of good - evil, life - death.